Human Resource Planning (HRP): A Theoretical Study - M Ghani Rizki Mei Vani; M Syahri Ramadhan; Selvia Oktarina; Cinta Wati (Penerbit dan Percetakan CV. Picmotiv, 2025)
This study aims to explore in depth the concept, process, and benefits of human resource planning (HRP) within organizations. Using a qualitative literature review method, this research collects and analyzes various sources such as textbooks, academic journals, and research articles. The results show that HR planning is a strategic process involving labor needs analysis, demand and supply forecasting, availability assessment, action plan formulation, and evaluation and control. Effective HR planning enables organizations to align workforce needs with required competencies, optimize productivity, and enhance competitiveness amid dynamic business changes. Therefore, HR planning serves not only as an administrative tool but also as a strategic instrument to achieve the organization’s long-term goals.